Contribuição ao conhecimento dos Agathidinae (Hymenoptera, Braconidae) da fauna brasileira - Campos, Giulia Yurie Iza de (2021)
The order Hymenoptera is one of the most numerous and diverse among the insects’ group and is represented by ants, wasps, and bees. The parasitoid wasps present ecological importance for being top predators, biological control agents and bioindicators of preserved areas as well as economic importance for attack Lepidoptera larvae, many of which, with agricultural relevance. The subfamily Agathidinae is a moderately large group of the family Braconidae, presenting 26 New World genera. In order to analyze diversity of these wasps in the Coleção Taxonômica do Departamento de Ecologia e Biologia Evolutiva da UFSCar (DCBU), it was conducted a study that identified 1033 Agathidines from 13 genera: Aerophilus Szépligetti, Agathis Latreille (first record for Brazil); Alabagrus Enderlein, Amputoearinus Sharkey, Cremnops Förster, Earinus Wesmael, Hemichoma Enderlein (first record for Brazil), Lytopylus Förster, Sesioctonus Viereck (first record for Brazil), Therophilus Wesmael, Trachagathis Viereck, Zamicrodus Viereck, and Zelomorpha Ashmead. Through the results it was possible to elaborate location maps for each genera and charts relating the percentage of individuals with the seasons and biomes in which they were collected. The study allowed to: (1) contribute to the knowledge of Brazilian Braconidae; (2) register three unprecedent Agathidinae genera in the country; (3) identify new species and (4) register the collection methods, seasons, and collection sites of the material studied.